Exogenous Application of Antioxidants on Leaf Chlorophyll, Yield Dynamics and Berry Quality of Sweet Pepper (Capsicum annuum L.) - Rahman, Md Saidur; Akter, Mahmoda; Chowdhury, Md Shah Newaz; Rahman, Md Mofizur; Munshi, Mostarak Hossain (International Journal of Sustainable Agricultural Research, 2020)
An experiment was carried out to investigate the influences of seven levels of antioxidants on BARI Mistimorich-1 and BARI Mistimorich-2 varieties of sweet pepper at the Central Research Farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh. Antioxidants were applied to sweet pepper varieties which had a significant effect on physiology, yield and quality of sweet pepper. Among those treatments, ascorbic acid (AA) at 200 ppm with salicylic acid (SA) at 200 ppm was more potential to enhance chlorophyll a (30%), chlorophyll b (39.39%), total chlorophyll (33.73%), number of flower plant-1 (17.63%), number of fruits plants-1 (56.73%), fruit yield plant-1 (43.61%), total soluble sugar (28.67%) and vitamin C (22.75%) compare to control. The variety of BARI Mistimorich-2 produces 4.55% higher fruit yield than BARI Mistimorich-1. Among those antioxidants, AA at 200 ppm with SA at 200 ppm demonstrate the best potentiality to solved flower and fruit dropping problems and ultimately lead to higher production of sweet pepper.